Perbandingan Deteksi Tepi Citra Digital dengan Menggunakan Metode Prewitt, Sobel dan Canny - Sukatmi Sukatmi (Puslitbang Kopertip Indonesia, 2017)
Edge detection of is a process that aims to detect line the edge that limits two areas image. Writing this will discuss about the comparison detection the edge of digital image with the methods prewitt, sobel and canny with programming matlab. The detection of the edge of done with detect 6 (six) digital image namely hestain.png , onion.png , saturn.png , tape.png , tissue.png and toysflash.png. Sweep edge indicated by many white pixel show detection edge of the process .The results show that for the detection the image of digital canny better method of the sobel and methods sobel better than prewitt method.